Socio-Demographic Predictors of Traditional Birth Attendant Utilization Among Women in Ondo State, Nigeria - Olasunkanmi Rowland Adeleke (Utan Kayu Publishing, 2026)
Traditional Birth Attendants (TBAs) continue to help in deliveries in several Nigerian communities contributing to high maternal mortality despite global initiatives to encourage skilled birth attendance. This study investigate the socio-demographic predictors of use of Traditional Birth Attendants in Akoko Area of Ondo State, Nigeria. A descriptive cross-sectional study was conducted with 425 women of childbearing age (15-49 years) who had given birth in the past 5 years. Women who met the criteria were selected the criteria using a multi-stage sampling technique. A validated structured questionnaire was used to collect data which were analyzed using descriptive statistics, chi-square, and binary logistic regression at a significance level of 5%. Out of 425 women, 163 (38.4%) had their last delivery assisted by a TBA. Important predictors of TBA use were maternal age of 35 years and above (AOR=2.45, 95% CI: 1.52-3.95); having no formal education (AOR=4.12, 95% CI: 2.28-7.45); having a monthly income of below ₦20,000 (AOR=2.89, 95%CI: 1.74-4.80); having four or more children (AOR=2.23, 95% CI: 1.38-3.60); and having to travel more than 30 minutes to a health facility (AOR=2.67, 95% CI:1.65-4.32). Most women cited cost (72.4%), culture (65.0%), spiritual (62.3%) and convenient (58.9%) as the primary reasons for using TBAs. The study finds a high level of use of traditional birth attendants for last delivery. Predictors included older mothers, having no formal education, and poor household income, having many children, and long distances to health facilities. The main motivation for selecting TBAs was their low cost, culture, spirituality, and access.